Rhetoric of Female Voices against Patriarchy in A Doll’s House - Neupane, Dipesh (Pursuits: A Journal of English Studies, 2024)
This article tries to explore the female subjugation in Henrik Ibsen’s A Doll’s House. Women confronts female domination, torture and other different domestic violence in different societies of the world in different ways. They get misbehaved and branded as secondary persons in the family in many societies of the world. They remain far from the fundamental rights in some cases. In many societies, they face economic, political, social and cultural upheavals. The protagonist of the novel Helmer treats his wife as a doll rather than a vital member of the family. He wants to keep her under his control in every matter of the family though she sacrifices her life for him wholeheartedly. Seeking emancipation in her family, Nora leaves her home, which marks the feminist voices against patriarchal domination prevalent in society. This article employs radical feminism proposed by Ti-Grace Atkinson. Society is a patriarchy in which the class of man is the oppressors of the class of woman. They oppose that the oppression of woman is the most fundamental form of oppression.